Selected economic theories’ point of view on the business model transformation - Ulrichová, Veronika; Očko, Martin (Vysoké učení technické v Brně, Fakulta podnikatelská, 2024)
Purpose of the article: The purpose of this article is to introduce and explain the economic difficulty of transforming a company’s business model and examine the change through selected economic theories. Methodology/methods: The methodology for the conduction of this paper is based on the review of the original resources and writings of the people who have been influencing the economic thought of humankind. Scientific aim: This paper aims to analyze the impact of the business model transformation using various economic theories. It offers the points of view of authors such as John Maynard Keynes, Friedrich Hayek and Joseph Schumpeter, considering the current circular economy trends. The whole paper is based on the implications of the theories to the proposed dissertation topics of the authors. Findings: This paper implies that sustainability and servitization are complex processes that require transformation of business models and implementation of digital technologies. Whether sustainability is truly perceived as sustainable depends on the constant increase in globalization and the associated increase in resource demand, which directly influences the level of emissions and waste production. Conclusions: This paper points out that in the current modern digital era, companies need to actively analyze their market environment, taking into account competitors' activities, financial constraints, economic situation and the stage of the business cycle. Society is placing ever-increasing demands on companies to behave sustainably, be environmentally responsible, and require companies to address the impacts of their activities, including the use of renewable resources and recycling standards. The integration of digital technologies and the focus on sustainability in this paper highlights the interconnection of servitization, business model transformation and digitalization in modern manufacturing strategies.
Keywords: servitization; sustainability; business model; transformation; circular economy; digitalization